Norma sosial dalam ruang digital: Bagaimana media sosial mengubah perilaku dan etika komunikasi di kalangan remaja - puspita sari, rossalita rossalita (Maliki Interdisciplinary Journal, 2026)
Social media has become an integral part of adolescents' daily lives, providing a platform for interaction, information sharing, and self-expression. This study aims to analyze changes in social communication behavior and norms among adolescents as a result of the integration of social media into daily life. Using a descriptive qualitative approach to examine digital interaction practices, the results indicate online disinhibition that has led to increased ethical challenges, including cyberbullying, the spread of disinformation, and cancel culture. It was found that communication norms in digital spaces differ substantially from face-to-face interactions, often ignoring the principles of privacy and respect. As a discussion and conclusion, there is a great urgency to increase awareness of digital communication ethics among adolescents. Support and learning from the social environment (family and peers) are essential for adolescents to use social media positively and responsibly for the development of self-identity, rather than as a source of ethical problems.